A decision support tool for assessing risks to above-ground river pipeline crossings. Issue 2 (14th August 2019) - Maniatis, Georgios; Williams, Richard D.; Hoey, Trevor B.; Hicks, John; Carroll, William
Abstract : Infrastructure assets require suitable management and assessment protocols due to age-related deterioration, extreme weather events and climate change impacts. Above-ground river crossings are weak links in pipe networks since bank erosion and scour can undermine the integrity of built structures. A simple protocol was developed to assess river bank stability in the vicinity of river pipeline crossings. The erosion risk index (ERI) follows established bank erosion estimation techniques, adapted for users who are not trained geomorphologists. Calculation of the ERI is based on analysis of photographs acquired during an optimised inspection protocol using a custom app on a ruggedised tablet computer. The ERI was tested across Scotland and proved to be adequate for a first-order geomorphological assessment and to provide a classification of crossings according to susceptibility to river bank erosion. The ERI is transferable, with appropriate testing, to other infrastructure river crossing networks in the UK and beyond. The methodology used to develop and test the ERI is applicable to the development of other protocols to manage and assess infrastructure assets.